DEFENSE MECHANISM DUE TO MIA’S ANXIETY IN PRINCESS DIARIES USING FREUDIAN PSYCHOANALISIS - Milenti Renanda Paratu; Anna Sriastuti (International Journal of Social Science, 2025)
This study explores the psychological struggles of Mia Thermopolis in The Princess Diaries using Sigmund Freud’s psychoanalytic theory. The analysis focuses on Mia’s anxiety as she transitions from an ordinary teenager to the heir of the Genovian throne. Freud’s model of the id, ego, and superego is used to understand the conflict between Mia’s personal desires and societal expectations. Her id craves a normal teenage life, while her superego demands that she fulfill her royal duties. The ego attempts to balance these opposing forces, leading to intense anxiety and self-doubt. Furthermore, the study examines Mia’s use of defense mechanisms such as repression and sublimation to cope with her psychological distress. Through a qualitative approach, this research highlights how unresolved inner conflicts shape Mia’s character development, offering a deeper understanding of anxiety in young adult literature